Burden of illness in people with medically refractory epilepsy who suffer from daily to weekly seizures: 12-month follow-up of participants in the EPISODE study - van Hezik-Wester, Valérie; de Groot, Saskia; Kanters, Tim; Versteegh, Matthijs; Wagner, Louis; Ardesch, Jacqueline; Brouwer, Werner; van Exel, Job (Frontiers in Neurology, 2022)
Background A small group of people with epilepsy suffers from frequent seizures despite the available pharmacological and non-pharmacological interventions. The impact of epilepsy on these people extends beyond health-related quality of life (HRQoL), impacting a person's broader well-being and ability to participate in society. This study describes the burden of medically refractory epilepsy in people who suffer from daily to weekly seizures, in terms of HRQoL, well-being, and societal costs. Methods Data from the EPISODE study on (cost-) effectiveness of seizure dogs for adults with severe medically refractory epilepsy were used, collected in 25 patients during the first 12 months before they were partnered with a certified seizure dog. Data comprised seizure diaries covering 365 days and five three-monthly surveys, including the EQ-5D-5L, QOLIE-31-P, and ICECAP-A to measure HRQoL and well-being. A societal perspective was applied to estimate costs using the iMCQ and iPCQ questionnaires about healthcare use, informal care, and productivity losses. Results Daily seizure frequency and survey data were collected in 25 patients. A minimum of 114 observations was available for each instrument included in the survey. A total of 80% of participants experienced seizures on three or more days per week, with a median ranging from 1 to 17 seizures per seizure day. The mean EQ-5D-5L utility score was 0.682 (SD 0.235), which is considerably lower than the age-adjusted general population average. The mean QOLIE-31-P and ICECAP-A scores were 55.8 (SD 14.0) and 0.746 (SD 0.172), respectively. The average annual total cost amounted to €39,956 (range €3,804–€132,64). Informal care accounted for the largest share of costs (50%); those who received informal care reported, on average, 26 h per week (SD 30). Conclusions Severe medically refractory epilepsy is associated with a considerable burden of illness at the patient and societal level. People with this condition have significantly reduced HRQoL and well-being and are limited in their ability to work while having substantial medical costs and a strong dependency on informal care.